Market access: Ensuring product quality and customer confidence [Tanzania] - Suleiman, Suleiman (Technical Centre for Agricultural and Rural Cooperation, 2018)
In Zanzibar, an Agriculture Sector Development Programme-Livestock (ASDP-L) is enhancing the access if rural agricultural households to improved agricultural production technologies, increasing household food security and incomes. Through business coaching and farmer field school training, fruit and vegetable growers are learning how to add value to and ensure good quality of their produce.